Meta-heuristic multi- and many-objective optimization techniques for solution of machine learning problems - Rodrigues, Douglas; Papa, Joao P. [UNESP]; Adeli, Hojjat (Wiley-Blackwell, 2017)
Recently, multi- and many-objective meta-heuristic algorithms have received considerable attention due to their capability to solve optimization problems that require more than one fitness function. This paper presents a comprehensive study of these techniques applied in the context of machine learning problems. Three different topics are reviewed in this work: (a) feature extraction and selection, (b) hyper-parameter optimization and model selection in the context of supervised learning, and (c) clustering or unsupervised learning. The survey also highlights future research towards related areas.
Keywords: machine learning; meta-heuristic algorithms; multi-objective optimization